Is The “U-Sign” Radiologic Feature Of A Posterior Cruciate Ligament Tibial Avulsion Fracture? - Piedade, Sergio Rocha; Ferreira, Daniel Miranda; Hutchinson, Mark; Maffulli, Nicola; Mischan, Martha Maria [UNESP]; Neyret, Philippe (FapUNIFESP (SciELO), 2021)
Objective: By analyzing our cases of posterior cruciate ligament (PCL) tibial avulsion fracture, we noted that a U-shaped image was present in the anteroposterior plain radiographs view of the affected knee, even in cases where the profile view of the knee had been inconclusive as to tibial PCL avulsion fracture, a “hidden” fracture. Therefore, we aimed to investigate whether there was an anatomical correlation between this radiological U sign and the tibial insertion of the PCL and to ascertain the intra and inter-rater reliability of this sign in clinical practice. Methods: The data of the widths and heights area of the PCL tibial insertion area, and the U sign area were measured and compared to the largest width of the tibia. Two moreover, the reliability and reproducibility of this imaging were analyzed. Results: The areas height of the U-sign area and the anatomical insertion area of the posterior cruciate ligament showed no difference, and both were topographically located in the two central quarters of the proximal end of the tibia. The radiographic assessment showed excellent Kappa agreement rates between interobserver and intraobserver, with high reliability and reproducibility. Conclusion: The U sign is a radiographic feature of PCL tibial avulsion fracture seen on the radiograph AP view, there is a high association between the ratios of the U-sign area height in the X-ray and the anatomical height of the PCL tibial insertion site MRI with the largest width of the proximal tibia. The radiographic U sign showed excellent rates of interobserver and intraobserver agreement with Kappa values higher than 0.8. Level of Evidence IV; Dignostic Studies – Investigating a Diagnostic Test.
A Imagem Do “U-Radiológico” É Um Sinal Da Fraturaavulsão Tibial Ligamento Cruzado Posterior?
Keywords: Diagnosis; Fractures Avulsion; Knee; Posterior Cruciate Ligament; Radiography